The Influence of Perceived Quality and Price Fairness on Repurchase Intention through Customer Satisfaction of Yonex Badminton Racket Users - Roland Franklin; Heriyadi Heriyadi; Ahmadi Ahmadi; Wenny Pebrianti; Bintoro Bagus Purmono (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the effect of perceived quality and price fairness on repurchase intention with customer satisfaction as a mediating variable among Yonex badminton racket users in Indonesia. The study employed a quantitative approach with a causal research design. Data were collected through a Likert-scale questionnaire distributed to 250 respondents using purposive sampling. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS 4.0. The results indicate that perceived quality has a significant direct effect on customer satisfaction and repurchase intention. Price fairness is also found to have a significant effect on customer satisfaction and repurchase intention. In addition to these direct effects, customer satisfaction serves as a partial mediator that strengthens the influence of perceived quality and price fairness on repurchase intention. These findings suggest that consumers consider not only quality and price directly, but also evaluate them through their level of satisfaction before deciding to repurchase. Accordingly, this study emphasizes customer satisfaction as an important psychological mechanism that links consumers’ perceptions of quality and price to repurchase behavior.